2016
DOI: 10.1007/s00420-016-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving fit to work assessments for rail safety workers by exploring work limitations

Abstract: PurposeWe aim to provide evidence for improving fit to work assessments for rail safety workers and raised the question whether adding an assessment of work limitations is useful. Therefore, we assessed differences in the proportions of perceived work limitations and reported health complaints and whether older age or having health complaints are risk factors for having work limitations.MethodsJob requirements for rail safety workers are ‘vigilance and clear judgment’, ‘good communication abilities’, ‘sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Examples of job-specific medicals developed with the ‘ new why ’, ‘ how ’ and ‘ what ’ in the last decade have led to the modernization of mandatory medicals in our department for ambulance workers [ 9 ], firefighters [ 10 ], hospital physicians [ 11 ], rail safety workers [ 12 ] and workers in the construction industry [ 13 ]. This revised way of performing medical examinations has had a different impact on the practice of occupational physicians.…”
mentioning
confidence: 99%
“…Examples of job-specific medicals developed with the ‘ new why ’, ‘ how ’ and ‘ what ’ in the last decade have led to the modernization of mandatory medicals in our department for ambulance workers [ 9 ], firefighters [ 10 ], hospital physicians [ 11 ], rail safety workers [ 12 ] and workers in the construction industry [ 13 ]. This revised way of performing medical examinations has had a different impact on the practice of occupational physicians.…”
mentioning
confidence: 99%
“…Kesiapan kerja perlu diukur untuk memastikan seluruh pekerja berada dalam kondisi bugar untuk melaksanakan tugas secara efektif, dan tidak melakukan aktivitas yang berbahaya bagi diri sendiri dan masyarakat sekitar [11], [12]. Pengukuran kesiapan kerja dapat membantu pekerja untuk memperhatikan kesehatan dirinya sendiri, mendeteksi dan memperbaiki kondisi kerja, serta menghimpun data yang terkait dengan kondisi pekerja [13].…”
Section: Pendahuluanunclassified
“…It is shown that the largest number of accidents in railway transport and errors in the train driver's actions in Europe [5], China [6], South Korea [7] and Japan [8] is associated with human factor. Therefore, monitoring the health status of the members of train crews as well as identifying the factors of the potential risk among them is an integral part of the medical aspects of the rail transport safety [9,10].…”
Section: Introductionmentioning
confidence: 99%